Temporal Characterization of Microglia-Associated Pro- and Anti-Inflammatory Genes in a Neonatal Inflammation-Sensitized Hypoxic-Ischemic Brain Injury Model. (2nd March 2022) - Bernis, Maria E.; Schleehuber, Yvonne; Zweyer, Margit; Maes, Elke; Felderhoff-Müser, Ursula; Picard, Daniel; Sabir, Hemmen
Abstract : Hypoxic-ischemic encephalopathy (HIE) mainly affects preterm and term newborns, leading to a high risk of brain damage. Coexisting infection/inflammation and birth asphyxia are key factors associated with intracerebral increase of proinflammatory cytokines linked to HIE. Microglia are key mediators of inflammation during perinatal brain injury, characterized by their phenotypic plasticity, which may facilitate their participation in both the progression and resolution of injury-induced inflammation. The purpose of this study was to investigate the temporal expression of genes associated with pro- and anti-inflammatory cytokines as well as the nucleotide-binding domain, leucine-rich repeat protein (NLRP-3) inflammasome from microglia cells. For this purpose, we used our established neonatal rat model of inflammation-sensitized hypoxic-ischemic (HI) brain injury in seven-day-old rats. We assessed gene expression profiles of 11 cytokines and for NLRP-3 using real-time PCR from sorted CD11b/c microglia of brain samples at different time points (3.5 h after LPS injection and 0, 5, 24, 48, and 72 hours post HI) following different treatments: vehicle, E. coli lipopolysaccharide (LPS), vehicle/HI, and LPS/HI. Our results showed that microglia are early key mediators of the inflammatory response and exacerbate the inflammatory response following HI, polarizing into a predominant proinflammatory M1 phenotype in the early hours post HI. The brains only exposed to HI showed a delay in the expression of proinflammatory cytokines. We also demonstrated that NLRP-3 plays a role in the inflammatory resolution with a high expression after HI insult. The combination of both, a preinfection/inflammation condition and hypoxia-ischemia, resulted in a higher proinflammatory cytokine storm, highlighting the significant contribution of acute inflammation sensitizing prior to a hypoxic insult on the severity of perinatal brain damage.